THE EFFECTIVENESS OF MIND MAPPING AND BRAINSTORMING TECHNIQUES TO TEACH WRITING TO VISUAL AND READ WRITE LEARNING STYLE STUDENTS - Setiawan, Fiki (Syntax Literate, 2019)
This research was conducted to investigate the effectiveness of Mind Mapping andBrainstorming technique used by students with visual and read-write learning style.The subject of the study was the students of Akademi Analis Kesehatan An Nasherin academic year 2018/2019. The subjects were the students of class A and B,divided into two parts of learning style namely visual and read-write. This researchuses 2x2 factorial experimental design. The object of this research was the teachingof analytical exposition text. The instruments used were a test, questionnaire, andobservation. The finding of this research indicates that mind mapping andbrainstorming strategies were effective in teaching writing to the students withvisual and read-write learning style. The result showed that the score of mindmapping strategy was higher than brainstorming strategy. The conclusion of thisresearch has proven that mind mapping technique and brainstorming techniquecan help and improve the students in writing skill for both students with visual andread-write learning style. It can be concluded that mind mapping strategy wasmore effective than brainstorming strategy and there was interaction among thetechnique, writing skill, and students learning style. It is hoped that the studentsand the teacher can use that technique in teaching and learning process.Keywords: Brainstorming, Mind Mapping, Visual and Read Write Learning Style